Urban inscriptions: A discipline in the horizon of citizenship - Correa, Thiago Moreira [UNESP] (My University, 2020)
We take into consideration the role of São Paulo city hall’s public policies to reflect on the importance of integrating urban inscriptions in Higher Education disciplines in Brazil. According to the historical summary presented, the pendulum swing of rejection and acceptance by the mayors of São Paulo generates avoidable costs and the exclusion of an institutional approach regarding urban inscriptions practices. In order to have efficient public policies, we observed that the academic inclusion of themes specifically linked to urban inscriptions might result in support of professions that directly interact with the practices (Architecture, Urbanism, Arts, etc.); it can also increase the diffusion of knowledge in Basic Education, and highlight the need to institutionally integrating the urban inscriptions into the dynamics of cities and the citizenship formation.
Keywords: Education; Public Policies; São Paulo; Urban Inscriptions